Kajian Elastisitas Transmisi Harga dalam Pemasaran Ternak Sapi Potong di Kabupaten Timor Tengah - Bay, Arni Rosmawati; Lalus, Matheos F.; Deno Ratu, Maria R.; Sogen, Johanes G. (Animal Agricultura, 2024)
This study aims to analyze price transmission elasticity, farmer's share, and marketing margins in the beef cattle distribution chain in Timor Tengah Selatan (TTS) Regency. A survey method was employed to collect data related to the marketing chain. The results showed that the price transmission elasticity value was 1.2237, indicating that the rate of price changes at the farmer level was higher than at the trader level. The marketing margin obtained by sub-district traders was IDR 1,005,014, while district traders obtained a margin of IDR 1,640,762. The farmer's share was 89% when cattle were sold to sub-district traders and 84% when sold to district traders. In conclusion, high price transmission elasticity (Et > 1) indicates an imbalance in price distribution along the marketing chain, the farmer's share for cattle farmers in TTS Regency was relatively high, particularly when selling to sub-district traders, and the marketing margin reflects the relative efficiency of different marketing channels, with IDR 2,645,776 in marketing channel I and IDR 1,640,762 in marketing channel II.